ANALISIS KEMAMPUAN LITERASI MATEMATIKA MELALUI PENYELESAIAN SOAL PISA PADA SISWA DI SMP YANG BERUSIA 15 TAHUN - ANNUR, MUHAMMAD FIRMAN; YOHANES, YOHANES (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2024)
This study was to determine the mathematical literacy abilities of 15 year old students in solving PISA (Program for International Student Assessment) questions at SMP Negeri 3 Sengah Temila. The research model used is descriptive research with a qualitative approach. The subjects in this study were 15-year-old students at SMP Negeri 3 Sengah Temila as many as 9 subjects with the selection based on correct test results, and based on subjects who met at least level 1 indicators. Data collection techniques were in the form of test instruments and interviews. The data obtained was then analyzed through 3 stages of data analysis, namely data reduction, data presentation and drawing conclusions. The results of the study concluded that the mathematical literacy abilities of 15-year-old students in solving PISA questions at SMP Negeri 3 Sengah Temila at level 1 were classified as good with an acquisition of 75%, at level 2 they were sufficient with an acquisition of 50%, at level 3 they were classified as lacking with an acquisition a score of 33%, and at level 4 it is classified as very poor with a score of 17%. While level 5 and level 6 are said to not exist because students are unable to meet the level 5 and level 6 indicators. ABSTRAKPenelitian ini untuk mengetahui kemampuan literasi matematika siswa yang berusia 15 tahun dalam penyelesaian soal-soal PISA (Programme for International Student Assessment) di SMP Negeri 3 Sengah Temila. Model penelitian ini yang digunakan adalah penelitian deskriptif dengan pendekatan kualitatif. Subjek pada penelitian ini adalah siswa yang berusia 15 tahun di SMP Negeri 3 Sengah Temila subjek sebanyak 9 orang dengan pemilihan berdasarkan hasil tes yang sudah benar, dan berdasarkan subjek yang memenuhi minimal indikator level 1. Teknik pengumpulan data berupa instrumen tes dan wawancara. Data yang diperoleh kemudian dianalisis melalui 3 tahapan analisis data, yaitu reduksi data, penyajian data dan penarikan kesimpulan. Hasil penelitian menyimpulkan kemampuan literasi matematika siswa yang berusia 15 tahun dalam penyelesaian soal-soal PISA di SMP Negeri 3 Sengah Temila pada level 1 tergolong baik dengan perolehan 75%, pada level 2 tergolong cukup dengan perolehan 50%, pada level 3 tergolong kurang dengan perolehan skor 33%, dan pada level 4 tergolong kurang sekali dengan perolehan skor 17%. Sedangkan level 5 dan level 6 dikatakan tidak ada dikarenakan siswa tidak mampu memenuhi indkator level 5 dan level 6.